Doping: argumentos em discussão - Otávio Tavares (Universidade Federal do Rio Grande do Sul, 2002)
The use of doping is one of the major issues of contemporary sport. The solution of the drug-taking problem seems to be distant despite the almost hegemonic opinion against doping. If arguments should correspond practical consequences, the aim of this paper is to exam the arguments against doping in sportin terms of their logic. We tried to demonstrate through questions and comparisons that those arguments are not valid since they do not correspond practical consequences. Finally we try to focus doping against the symbolic dimension ofsport.